Pluto's Beating Heart Regulates the Atmospheric Circulation: Results From High‐Resolution and Multiyear Numerical Climate Simulations. Issue 2 (10th February 2020) - Bertrand, T.; Forget, F.; White, O.; Schmitt, B.; Stern, S. A.; Weaver, H. A.; Young, L. A.; Ennico, K.; Olkin, C. B.
Abstract: Pluto's atmosphere is mainly nitrogen and is in solid‐gas equilibrium with the surface nitrogen ice. As a result, the global nitrogen ice distribution and the induced nitrogen condensation‐sublimation flows strongly control the atmospheric circulation. It is therefore essential for Global Climate Models to accurately account for the global nitrogen ice distribution in order to realistically simulate Pluto's atmosphere. Here we present a set of new numerical simulations of Pluto's atmosphere in 2015 performed with a Global Climate Model using a 50‐km horizontal resolution (3.75° × 2.5°) and taking into account the latest topography and ice distribution data, as observed by the New Horizons spacecraft. In order to analyze the seasonal evolution of Pluto's atmosphere dynamics, we also performed simulations at coarser resolution (11.25° × 7.5°) but covering three Pluto years. The model predicts a near‐surface western boundary current inside the Sputnik Planitia basin in 2015, which is consistent with the dark wind streaks observed in this region. We find that this atmospheric current could explain the differences in ice composition and color observed in the northwestern regions of Sputnik Planitia, by significantly impacting the nitrogen ice sublimation rate in these regions through processes possibly involving conductive heat flux from the atmosphere, transport of dark materials by the winds, and surface albedo positive feedbacks. In addition, we find that this current controls Pluto's general atmospheric circulation, which is dominated by a retrorotation, independently of the nitrogen ice distribution outside Sputnik Planitia. This exotic circulation regime could explain many of the geological features and longitudinal asymmetries in ice distribution observed all over Pluto's surface. Key Points: High‐resolution simulations of Pluto's climate show that the circulation is dominated by ∼ 10‐m/s retrograde winds during most of the year Nitrogen condensation‐sublimation flows in Sputnik Planitia are creating an intense western boundary current Atmospheric heat flux, transport of tholins, and albedo feedbacks could explain the albedo contrasts observed in Sputnik Planitia